The Spontaneous Spinal Epidural Hematoma in Children: Two Case Reports and a Literature Review - Gordon-Gullanyi, Ayisi; Encarnacion-Santos, Daniel A; Chmutin, Gennady; Lobankin, Pavel; Chmutin, Egor; Berdinov, Farkhad; Annanepesov, Nazar; Musa, Gerald; Mametgulyyeva, Meryem; Chaurasia, Bipin; Nikolaevich-Umerenkov, Victor (Journal of Endovascular Resuscitation and Trauma Management, 2025)
Background: Spontaneous Spinal Epidural Hematoma (SSEH) is a rare emergency in the general population. It is an even rarer entity in the pediatric population. Case Description: We report two cases: a 15-month-old boy with SSEH, who was presenting with irritability, acute pain, and a 3-year-old girl who presented with left-sided Horner’s syndrome and pain in the left upper extremity. Both patients were misdiagnosed upon admission. At 10 months and 2 months, respectively, after surgery, decompressive surgery was recommended as soon as possible, but this is normally carried out 12 to 24 hours after onset. Conclusion: The clinical presentation of SSEH is atypical and highly difficult to diagnose in children, especially in infants and toddlers. SSEH should always be included in the differential diagnosis when children present with acute back and neck pain, irritability, and uncontrolled crying.